Analysis of student participation in a school triathlon in the Region of Murcia (seasons 2011, 2012 and 2013) - Vílchez M. P. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2015)
Sports at school age are research objective in many studies. Concretely, triathlon is a sport that has a progressive growth (observed, for study, the participation on final triathlon events from seasons 2011, 2012 y 2013 is analyzed to know the characteristics of participation and to be able to guide promotion sports tasks of corresponding entities. A sample of 807 participations of scholars on final triathlon events from Region of Murcia was used (68.9% were boys and 31.3% were girls). It was concluded the need to target programs to promote this sport to age categories and gender that need it most. As future implementation, it is proposed a better communication between responsible entities and Physical Education teachers to increase commitment of participation by enrolling on school and a new improved system of entries.